World Politics and media framing: introducing the relevance of narratives in media outlet’s coverage about the Hong Kong protests - Menegazzi, Silvia (PARTECIPAZIONE E CONFLITTO, 2022)
This study deals with how narratives in world politics affect media framing in different contexts by analyzing the case of the Hong Kong-Mainland China conflict, with particular reference to the Hong Kong protests occurred in the years 2019-2020.The analysis suggests a scenario in which media covering is strongly affected by the power of discourse shaping world politics, which in the case of the Hong Kong protests, it stands as a direct result of the growing exacerbation between China and the United States.